2016
DOI: 10.1016/j.jpowsour.2015.11.043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coupled mass transport and internal reforming on modeling of solid oxide fuel cells part I: Channel-level model development and steady-state comparison

Abstract: Dynamic modeling and analysis of solid oxide fuel cell systems can provide insight towards meeting transient response application requirements and enabling an expansion of the operating envelope of these high temperature systems. SOFC modeling for system studies are accomplished with channel-level interface charge transfer models, which implement dynamic conservation equations coupled with additional submodels to capture the porous media mass transport and electrochemistry of the cell. Many of these models may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Chemical engineering, beginning in the late 19th century and impinging on aspects of industrial life, , is the study of momentum, energy, and mass transfer based on nonlinear coupled chemical reactions. It emphasizes the processing optimization of unit operation, such as stirring, separation, and purification, following new rules different from traditional laboratory chemistry. Similar to industrial-scale chemical engineering, mass transfer and surface reaction are also significant for heterogeneous electrocatalysis at the nanoscale. Mesoscopic electrocatalysis, a novel and popular research subject nowadays, is the study of the relationship between the overall electrocatalytic performances with the reaction conditions between the element and system scales .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chemical engineering, beginning in the late 19th century and impinging on aspects of industrial life, , is the study of momentum, energy, and mass transfer based on nonlinear coupled chemical reactions. It emphasizes the processing optimization of unit operation, such as stirring, separation, and purification, following new rules different from traditional laboratory chemistry. Similar to industrial-scale chemical engineering, mass transfer and surface reaction are also significant for heterogeneous electrocatalysis at the nanoscale. Mesoscopic electrocatalysis, a novel and popular research subject nowadays, is the study of the relationship between the overall electrocatalytic performances with the reaction conditions between the element and system scales .…”
Section: Results and Discussionmentioning
confidence: 99%
“…One-dimensional, plug flow, interface charge transfer models have been thoroughly investigated in the SOFC literature 18,19,22,23,37,38 and calibrated against button cell experiments to develop computational modeling tools capable of aiding in the system design process. A similar approach is adopted here, however, some of the modeling assumptions typically employed in SOFC modeling are not valid for PCFCs, particularly in the lower temperature operating regime.…”
Section: Modeling Methodologymentioning
confidence: 99%
“…It has been shown that time constants associated with gas transport dynamics within porous electrodes, being on the order of 10 −1 s, are simply much faster than thermal transport dynamics (order 10 2 -10 3 s). 17,23,[44][45][46] As shown in subsequent sections, the transient simulation studies reported here were conducted with current density ramps over 1s intervals; the effects of electrode gas dynamics will thus not be resolved due to the faster timescales for gas diffusion. Nevertheless, not including the transient effects of mass transport through the porous electrodes does not alter the predicted transient response of cells and stacks in terms of voltage, temperature, and power output, which are driven by the thermal response of the solid cell layers.…”
Section: Dynamic Conservation Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 When these pre-applicative cells are tested individually, single channel models are applied, which include the interconnectors and describe a single repeating unit (SRU). [14][15][16][17][18][19][20][21] Multi-dimensional models or finite element methods are utilized to capture the channel fluid dynamics, the patterns of the gas distribution under the interconnector ribs, or the diffusive transport in electrodes with graded porosity. Energy balances are introduced for the SRU, which frequently rely on the assumption of adiabatic channels, and on the attainment of local temperature equilibrium between the solid phase and the gas phase in the electrodes.…”
Section: List Of Symbolsmentioning
confidence: 99%